2017
DOI: 10.1098/rstb.2016.0232
|View full text |Cite
|
Sign up to set email alerts
|

Injury-mediated decrease in locomotor performance increases predation risk in schooling fish

Abstract: The costs and benefits of group living often depend on the spatial position of individuals within groups and the ability of individuals to occupy preferred positions. For example, models of predation events for moving prey groups predict higher mortality risk for individuals at the periphery and front of groups. We investigated these predictions in sardine () schools under attack from group hunting sailfish () in the open ocean. Sailfish approached sardine schools about equally often from the front and rear, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 39 publications
(51 reference statements)
0
39
0
Order By: Relevance
“…Billfish rostra have often been conjectured to facilitate prey capture (Fierstine, 1997;Fierstine and Voigt, 1996;Frazier et al, 1994), and this was confirmed in the case of sailfish, striped marlin and blue marlin (Domenici et al, 2014;Hansen et al, 2020;Shimose et al, 2007). Sailfish use their rostrum to slash or tap at fish, typically injuring prey before capture and ingestion (Domenici et al, 2014;Herbert-Read et al, 2016;Krause et al, 2017). Hansen et al (2020) compared the hunting behaviour of striped marlin and sailfish and concluded that striped marlins use their rostra less in prey capture and in particular slash less at fish schools.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Billfish rostra have often been conjectured to facilitate prey capture (Fierstine, 1997;Fierstine and Voigt, 1996;Frazier et al, 1994), and this was confirmed in the case of sailfish, striped marlin and blue marlin (Domenici et al, 2014;Hansen et al, 2020;Shimose et al, 2007). Sailfish use their rostrum to slash or tap at fish, typically injuring prey before capture and ingestion (Domenici et al, 2014;Herbert-Read et al, 2016;Krause et al, 2017). Hansen et al (2020) compared the hunting behaviour of striped marlin and sailfish and concluded that striped marlins use their rostra less in prey capture and in particular slash less at fish schools.…”
Section: Discussionmentioning
confidence: 94%
“…Third, sailfish introduce up to a third of their bill into prey schools before slashing or tapping (Domenici et al, 2014;Herbert-Read et al, 2016;Krause et al, 2017). The prey species have been found to not react to this insertion of the bill, despite being extremely close to the dangerous weapon (Domenici et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…When predators attack individual prey in groups, this risk will be related to the strategies that predators use when attempting to select targets from within the group. Previous empirical evidence shows that isolated individuals, or individuals on the edges of groups experience greater risk of predation (Duffield & Ioannou 2017, Ioannou et al 2019, Krause et al 2017, but these studies have also been limited to individuals' relative risk in a single plane. Further, most models investigating so-called 'marginal predation' have only considered this from a two-dimensional approach (Hamilton 1971, Hirsch & Morrell 2011, Viscido et al 2001.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of predation, however, is not distributed evenly across the different spatial positions an individual might occupy within the group. Risk can be higher for individuals on the group's edge rather than in the centre (also known as marginal predation: [3][4][5]), for individuals positioned further from their near neighbours [6][7][8], or for those at the front or back of moving groups [9][10][11]. The majority of evidence for the different risk afforded by different spatial positions comes from observational studies of real predators targeting real prey, and from how prey respond by changing their position in groups in response to predatory attacks [7,8,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%